2001
DOI: 10.1007/s001050051299
|View full text |Cite
|
Sign up to set email alerts
|

Erfolgreiche Therapie mit Tetracyclin und Nikotinaminsäure beim vernarbenden Pemphigoid

Abstract: We describe a case of cicatricial pemphigoid in a 92-year-old female with extensive mucocutaneous involvement. She developed extensive hemorrhagic blistering with severely bleeding lesions, that healed with scarring. The conjunctivae showed extensive synechia. The diagnosis was based on clinical and histopathological features as well as immunofluorescence findings and immunoblot analysis. There was no clinical response to topical corticosteroids. The patient was given tetracycline and nicotinamid and showed ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…[33][34][35] However,dapsone usage should be regularly followed with periodic blood studies because of the associated complication of hemolytic anemia. Other systemic medications, including immunosuppressive agents such as azathioprine, methotrexate, cyclophosphamide, levamisole, and mycophenolate mofetil may also prove beneficial in the treatment of pemphigoid, [36][37][38][39][40][41][42] Studies have shown that MMP can be treated efficiently with tetracycline derivatives or combination therapy of tetracycline and niacinamide. [39][40][41] Alternately, intravenous immunoglobulins, plasmapheresis, and Low-level laser therapy (LLLT) can also be used as a therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] However,dapsone usage should be regularly followed with periodic blood studies because of the associated complication of hemolytic anemia. Other systemic medications, including immunosuppressive agents such as azathioprine, methotrexate, cyclophosphamide, levamisole, and mycophenolate mofetil may also prove beneficial in the treatment of pemphigoid, [36][37][38][39][40][41][42] Studies have shown that MMP can be treated efficiently with tetracycline derivatives or combination therapy of tetracycline and niacinamide. [39][40][41] Alternately, intravenous immunoglobulins, plasmapheresis, and Low-level laser therapy (LLLT) can also be used as a therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%